EXERCICE : (2 + 1 + 1,5 + 1,5 = 6 pts)

On considère l’expression E = (2x + 5)2 – (2x + 5)(x – 3).
1. Développer et réduire E.
2. Calculer E pour x = 2 puis pour x = 3 .
3. Factoriser E.
4. Résoudre l’équation (2x + 5)(x + 8) = 0.

Merci d'avance

1

Réponses

  • Utilisateur Brainly
2014-05-29T21:08:21+02:00
1- E=(2x+5)^2-(2x+5)(x-3) \\ E=4x^2+20x+25-(2x^2-6x+5x-15) \\ E=4x^2+20x+25-2x^2+6x-5x+15 \\  E=2x^2+21x+40

2- Pour x=2
     
     E = (2*2+ 5)^2 - (2*2 + 5)(2- 3)  \\ E=(4+5)^2-(4+5)(-1) \\ E=9^2-9*(-1) \\ E=81-9 \\ E=72
   
   Pour x=3
 
      E=(2*3+5)^2-(2*3+5)(3-3) \\ E=(6+5)^2-(6+5)*0 \\  E=11^2-11*0 \\  E=121-0 \\ E=121

3- E = (2x + 5)^2-(2x + 5)(x -3) \\ E=(2x+5)(2x+5)-(2x+5)(x-3) \\ E=(2x+5)(2x+5-(x-3) \\  E=(2x+5)(2x+5-x+3) \\ E=(2x+5)(x+8)

4- (2x + 5)(x + 8) = 0
    2x+5=0 ou x+8=0
    2x=-5 ou x=-8
    x=-5/2 ou x=-8

S= {- 8 ; - 5/2}